Hybrid Learning : Desain Pembelajaran Praktikum Botani Tumbuhan Berpembuluh untuk Menunjang Kemampuan Literasi Digital Mahasiswa dalam Pembelajaran Tatap Muka Terbatas: (Hybrid Learning : Design of Practical Learning Design of Vascular Plant Botany For Increasing the College Student Digital Literacy On Limited Face to Face Learning) - Susy Amizera; Didi Jaya Santri; Nike Anggraini; Elvira Destiansari (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The pandemic of Covid-19 has caused the diversion of online learning which has an effect on practicum activities, especially in the vascular plant botany. The aims of this research are (1) to apply the design of vascular plant botany practicum activities in limited face-to-face learning through hybrid learning, and (2) to determine students' digital literacy skills through hybrid learning. The type of research used is qualitative research with descriptive methods. In this study, it will be described how the application of hybrid learning in vascular plant botany practicum activities that can support students' digital literacy skills. The results illustrate that there are three stages of learning in hybrid learning practicum activities, namely the preparation stage, the implementation stage and the presentation stage. In this regard. Students' digital literacy skills are categorized as high on the indicators of Ability to operate/access media and the ability to obtain information, but are categorized as moderate on the ability to communicate through digital media. Thus, hybrid learning practicum learning designs can be implemented in limited face-to-face learning and can also support students' digital literacy skills as prospective teachers to prepare students as prospective teachers in digital learning in the 4.0 era. Key words: Hybrid Learning, Practicum, Plant, Digital Literacy ABSTRAK Adanya pandemi Covid-19 menyebabkan pengalihan pembelajaran daring yang berpengaruh pada kegiatan praktikum mahasiswa khususnya pada mata kuliah botani tumbuhan berpembuluh. Adapun tujuan dari penelitian ini, yaitu (1) menerapkan desain kegiatan praktikum botani tumbuhan perbembuluh dalam pembelajaran tatap muka terbatas melalui hybrid learning, dan (2) mengetahui kemampuan literasi digital mahasiswa melalui hybrid learning. Jenis penelitian yang digunakan yaitu penelitian kualitatif dengan metode deskriptif. Pada penelitian ini akan digambarkan bagaimana penerapan hybrid learning pada kegiatan praktikum botani tumbuhan berpembuluh yang dapat mendukung kemampuan literasi digital mahasiswa Hasil penelitian menggambarkan bahwa terdapat tiga tahapan pembelajaran pada kegiatan praktikum secara hybrid learning, yaitu tahap persiapan, tahap pelaksanaan dan tahap presentasi. Berkaitan dengan hal tersebut. Kemampuan literasi digital mahasiswa terkategori tinggi pada indikator Kemampuan mengoperasikan/ mengakses media dan kemampuan memperoleh informasi, namun terkategori sedang pada kemampuan berkomunikasi melalui media digital. Dengan demikian, desain pembelajaran praktikum secara hybrid learning dapat dilaksanakan pada pembelajaran tatap muka terbatas dan juga dapat menunjang kemampuan literasi digital mahasiswa sebagai calon guru untuk mempersiapkan mahasiswa sebagai calon guru pada pembelajaran digital di era 4.0. Kata kunci: Hybrid Learning, Praktikum, Tumbuhan, Literasi Digital